2021
DOI: 10.31234/osf.io/2x3kg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An active inference account of skilled anticipation in sport

Abstract: Optimal performance in time-constrained and dynamically changing environments depends on making reliable predictions about future outcomes. In sporting tasks, performers have been found to employ multiple information sources to maximize the accuracy of their predictions, but questions remain about how different information sources are weighted and integrated to guide anticipation. In this paper, we outline how active inference, a unifying account of perception and action, explains many of the prominent finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 60 publications
(132 reference statements)
0
8
0
Order By: Relevance
“…Recent work has outlined how applying Bayesian brain perspectives (see Friston et al, 2017;Knill & Pouget, 2004;Rao & Ballard, 1999) to the study of sporting anticipation can help to explain how performers integrate and weight multiple sources of information to make predictions during time constrained tasks (see Gredin et al, 2018Gredin et al, , 2020Harris et al, 2021). In the present study, we used a Bayesian active inference model of perception to examine observers' contextual priors regarding likely ball bounce trajectories and their sensitivity to early postural cues from the kicker and ball flight trajectory.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent work has outlined how applying Bayesian brain perspectives (see Friston et al, 2017;Knill & Pouget, 2004;Rao & Ballard, 1999) to the study of sporting anticipation can help to explain how performers integrate and weight multiple sources of information to make predictions during time constrained tasks (see Gredin et al, 2018Gredin et al, , 2020Harris et al, 2021). In the present study, we used a Bayesian active inference model of perception to examine observers' contextual priors regarding likely ball bounce trajectories and their sensitivity to early postural cues from the kicker and ball flight trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from the current study extend knowledge of anticipation in sports by developing an understanding of precision-based weighting of information sources. Previous models of anticipation in sport have pointed to the use of contextual priors and online sensory input (Müller & Abernethy, 2012), discussed issues related to how these information sources are weighted based on reliability (Gray & Cañal-Bruland, 2018;Runswick, Roca, et al, 2020), and suggested a Bayesian approach to tackle this question (Gredin et al, 2018;Harris et al, 2021). However, the work presented in this study is the first to combine these narratives in the literature to investigate information integration processes in expert performers using a combination of empirical data and computational modelling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations